AN INITIAL ESTIMATION ON THE EFFECTS OF HOA BINH HYDROPOWER DAM ON THE COASTAL SEDIMENTARY ENVIRONMENT IN RED RIVER DELTA - Thanh, Tran Duc; Vinh, Vu Duy; Saito, Yoshiki; Chien, Do Dinh; Tu, Tran Anh (Vietnam Journal of Marine Science and Technology, 2008)
Ago, the total annual discharges of Red River approximately 135 bil.m3 water and 125 mil.ton suspended sediments. At the Son Tay station in main stream, the annual discharges were 114 bil. m3 water and 114 mil.ton suspended sediments, for which Da stream contributed a rate of 51% and 53% alternately. With the capacity of 9.5 bil.m3, the Hoa Binh hydropower Dam was completed to build in 1989 on the Da stream. After building the dam, a volume of 55 mil.ton sediments has been trapped on the bottom of reservoir, and the suspended sediment discharge at Son Tay Station is only 69 mil. ton/yr. The rates of water and sedimentary discharges which have transferred from the main stream of Red River through the Duong tributary into Thai Binh stream running off coastal area of North Do Son have obviously increased, and that is related to the operational regime of dam and hydrological features at river mouths. There has been a deep change in discharge and distributive rate of sediments at the coastal mouths of Red River. Before building the dam, the distribution of suspended sediment discharge was 113 mil.ton/yr in the south and 3 mil.ton/yr in the north of Do Son peninsular. This correlation has been 67 mil.ton/yr and 5 mil.ton/yr after building the dam. By calculation, the accreted rate of deltaic part of south Do Son is reduced from 27.4 m/yr down 14.7 m/yr. equivalent to reduce of 190 ha/yr. In fact, this has been indistinctive by the turbulent effects of other impacts, especially building quickly aquacultural ponds. However, it is notes that the unusual changes in erosion and accretion in some coastal sites, for example, the accreted rate at Ba Lat area reduced from 88.8m/yr down 58.7 m/yr, meanwhile the eroded rate of Hai Hau site increased from 8.6 m/yr. up 14.5 m/yr. The sediments supplied from eroded process in Hai Hau site have transported southwestward and made siltation of Lach Giang river mouth as shipping channel into the Hai Thinh harbor. The decrease of the extreme current in flood season by the operation of Hoa Binh dam has been a favourite condition for strengthening the longshore drift by wave action to deposit and to shallow the river mouths by the development of sandy shoals (Van Uc mouth), spits (Lach Giang mouth) or beach ridges (Day and Ba Lat mouths). After building the dam, the increase of suspended sediments and freshwater discharged from Cam and Nam Trieu tributaries locating in the North of Do Son is one the siltation cause for the shipping channel of Haiphong Port. The increase of suspended sediments and freshwater in the coastal area in North Do Son has made heavy impacts to coral reefs and biodiversity in Cat Ba-Ha Long area. Meanwhile, the coastal resort site in Do Son has suffered turbid effects leading to the looses of tourist economy. The Son La dam located upper Hoa Binh dam is being built and the coastal sedimentary environment of Red River delta will be more complicated when this construction project completed.